KONSEP PENDIDIKAN AKIDAH TERHADAP ANAK PERSPEKTIF M. QURAISY SYIHAB - Ainun Mahfudzah (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2017)
This research is motivated by the importance of education of aqidah. which is given to the children. The author is interested in doing this research because not everyone knows how to convey a good education about aqidah to children in accordance with the way of thinking . This thesis is written by exploring the thought of M. Quraisy Syihab related to the education of aqidah. The purpose of this study is to know the concept of education of faith towards children according to the perspective of M. Quraisy Syihab. This research uses the type of library research. This research is conducted by descriptive method and data analysis done with content analysis. The results of the analysis can be concluded that the goal of the Quraisy Syihab Perspective of educational of aqidah is reflected in the behavior and actions of a person in everyday life. The Quraisy Syihab perspective about education of aqidah’s material are the faith of Allah, the faith of the Prophet and the Apostle, the faith of the holly books of Allah, the faith of the Angel, Jin, and Satan, the faith of the Day of Judgment and the Hereafter, and Qada and Qadar. In explaining these materials, the methods used by M. Quraisy Syihab are question and answer method, amtsal (parable) method, and Quranic / Nabawi story method. In using these methods M. Quraisy Syihab also uses various media to make it easier for children to understand about education of aqidah. And that becomes an assessment of education of aqidah in M. Quraisy Syihab perspective is polite.